2021
DOI: 10.21273/horttech04658-20
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Bagging as an Alternative Technique for Enhancing Fruit Quality: A Review

Abstract: Preharvest factors such as poor orchard management and field sanitation can lead to pathological infection of the tree fruit being grown as well as insect pest infestation, resulting in poor postharvest fruit quality. Wind and hail damage may cause significant tree fruit abrasions and blemishes. Consequently, these preharvest factors may reduce yield and cause market and economic losses. One of the most successful methods used to manage tree fruit pathogens and insect infestation is the application of agrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…With this, there is an increased risk of sunburn, so removal of the bag must be done cautiously, possibly stepwise-for example, by using multi-layer bags [192]. Other benefits of pre-harvest bagging include a decreased incidence of sunburn [194,195], pest infestation and hail damage [196]. However, bagging fruit is laborious, so it requires a high-value product, a high-end market and/or a low labor cost for it to be economic.…”
Section: Baggingmentioning
confidence: 99%
“…With this, there is an increased risk of sunburn, so removal of the bag must be done cautiously, possibly stepwise-for example, by using multi-layer bags [192]. Other benefits of pre-harvest bagging include a decreased incidence of sunburn [194,195], pest infestation and hail damage [196]. However, bagging fruit is laborious, so it requires a high-value product, a high-end market and/or a low labor cost for it to be economic.…”
Section: Baggingmentioning
confidence: 99%
“…A previous study involving 'Granny Smith' apples thinned and paperbagged at golf ball size showed a reduced incidence of codling moth infestation to 0.4% and 1.3% compared with 2.5% and 24.5% during the 2 years of the study; no difference in codling moth infestation was observed in fruit that were and were not thinned (Bentley and Viveros, 1992). Other apple insect control using bagging has been reviewed by Buthelezi et al, (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nylon bags affected fruit quality, as indicated by the SSC, TA, and background color. Bags could be removed several weeks before harvest to improve fruit color (Buthelezi et al, 2021). Neither bag type was salvageable for reuse during the following season; therefore, they are not suitable for growers interested in sustainability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations